Lattice Boltzmann Approach for Local Reference Frames (Communications in Computational Physics, 2020)
In this paper we present a generalized lattice Boltzmann based approachfor sliding-mesh local reference frame. This scheme exactly conserves hydrodynamicfluxes across local reference frame interface. The accuracy and robustness of our schemeare demonstrated by benchmark validations.